Cost Recovery and Financial Viability of the Power Sector in Developing Countries : Insights from 15 Case Studies - Huenteler, Joern; Hankinson, Denzel; Rosenthal, Nicole; Balabanyan, Ani; Kochnakyan, Arthur; Nguyen, Tu Chi; Rana, Anshul; Foster, Vivien (World Bank, Washington, DC, 2020)
This paper analyzes power utilities in 15 jurisdictions to understand the determinants of success for reforms aimed at improving financial viability and cost recovery in the power sector and the impacts of these reforms on metrics of sector performance. The analysis finds that electricity tariffs are rarely high enough to cover the full costs of service delivery, even where the cost of service is low, and that few countries adequately manage volatile costs and maintain cost recovery levels over time. Almost everywhere, power utilities often impose a substantial fiscal burden and contingent liabilities on government budgets. Over the past 30 years, cost recovery levels have increased on average, but progress has been uneven, with over half of the case study jurisdictions experiencing a decline compared with the pre-reform period. The record of reforms of price formation, especially tariff setting through regulatory agencies, is mixed. On average, countries that have made more progress on utility governance and decision making perform better on cost recovery. The paper concludes with proposed modifications to the conceptual framework underpinning the economic analysis of power sector reforms as well as immediate, practical implications for understanding cost recovery as part of the overall power sector reform agenda.